2023
DOI: 10.1038/s41586-022-05546-8
|View full text |Cite
|
Sign up to set email alerts
|

Questioning the fetal microbiome illustrates pitfalls of low-biomass microbial studies

Abstract: Whether the human fetus and the prenatal intrauterine environment (amniotic fluid, placenta) are stably colonized by microbes in a healthy pregnancy remains the subject of debate. Here, we evaluate recent studies that characterized microbial populations in human fetuses from the perspectives of reproductive biology, microbiology, bioinformatics, immunology, clinical microbiology, and gnotobiology, and assess possible mechanisms by which the fetus might interact with microbes. Our analysis indicates that the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
112
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(141 citation statements)
references
References 143 publications
5
112
0
Order By: Relevance
“…Several studies have concluded that circulating bacteria, especially those found in healthy volunteers, are either traces of microbial DNA from external sources or organic remnants from non-living bacteria [ 79 , 80 ]. For similar reasons, the findings of the microbiome in other low-biomass environments such as the womb during pregnancy, brain and tumors have also been brought into question [ 81 , 82 ]. Indeed, NGS sequencing is very sensitive to capturing minute amounts of microbial DNA contaminants from extraction kits, storage containers, sequencing reagents and even the sequencer itself.…”
Section: Controversies and Counterclaimsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have concluded that circulating bacteria, especially those found in healthy volunteers, are either traces of microbial DNA from external sources or organic remnants from non-living bacteria [ 79 , 80 ]. For similar reasons, the findings of the microbiome in other low-biomass environments such as the womb during pregnancy, brain and tumors have also been brought into question [ 81 , 82 ]. Indeed, NGS sequencing is very sensitive to capturing minute amounts of microbial DNA contaminants from extraction kits, storage containers, sequencing reagents and even the sequencer itself.…”
Section: Controversies and Counterclaimsmentioning
confidence: 99%
“…Thirdly, there is an urgent need to establish the best practices and a standardized workflow for sample collection and processing, negative controls, and post-sequencing decontamination pipeline to enable data-sharing and inter-study comparison [ 81 ]. The gut microbiome is highly dynamic and labile to host and environmental factors such as host genetics, diet, medication, lifestyle and geographic regions [ 24 , 96 ].…”
Section: Knowledge Gaps and Future Directionsmentioning
confidence: 99%
“…It has to be acknowledged that analysis of the endometrial microbiome is hampered by multiple technical limitations and the low accessibility to healthy controls. Sequencing bias, originating from DNA/RNA contamination in laboratory reagents and extraction kits, is a major drawback in sequence-based studies, especially when studying low-biomass microbiota like that of the endometrium [ 16 , 17 , 18 ]. Sequencing of microbiota often gives only genus-level identifications with no information on which species are present.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, contaminations and annotation errors occurring at each step along the microbiome processing and analysis cascade may introduce artifacts and biases that are challenging to tackle and complicate the distinction between true and spurious biological signals. Understanding the scope, limitations, and confounders associated with each of these steps is essential for separating true signal from confounding factors, particularly in tissues with low or no microbial abundance [ 6 ]. Better harmonization of these methodologies, coupled with inclusion of multiple technical and biological controls, could enable more accurate interpretation of studies that can be generalized and reproduced across populations, geographies, genders, and ethnicities.…”
mentioning
confidence: 99%
“…Avoiding some of the field’s early technical missteps [ 6 ] while allowing innovative research to progress necessitates an appreciation of the extraordinary complexity and modularity of host–microbiome interactions, coupled with a much-needed modification of expectations. It is increasingly realized that diagnostic and therapeutic microbiome utilization in human disease will require a continued and, at times, painstaking and exhaustive exploration of molecular mechanisms and regulation, from overarching descriptive community associations to the microscale function of discrete bioactive therapeutic targets.…”
mentioning
confidence: 99%